ANALISIS KETERAMPILAN DASAR PADA METODE PEMBELAJARAN TEMATIK TERPADU DI KELAS 3 SDN MOJOMULYO 2 KABUPATEN SRAGEN - Kurnia Fitri Ramadani, Nazwa Fatimah Arrosyd, Alexsandrea Maharani Pringgo Darsono, Widia Wahana Kur (Elementary School and Education Journal, 2025)
This research aims to describe the basic skills of teachers in implementing integrated thematic learning methods, especially in natural science (IPA) learning content at SD Negeri 2 Mojomulyo in class 3. The method used is qualitative descriptive, with data collection through in-depth interviews with the class teacher as the main resource, documentation and literature study. The research results show that teachers apply various approaches, such as lectures, discussions, audio-visual media, and simple teaching aids to support students' understanding. Teachers also face various challenges, including students' unstable character and students' lack of courage in conveying understanding independently. Under these conditions, teachers continue to strive to evaluate students' overall understanding through oral tests and direct observation. This research recommends strengthening teacher soft skills professional training in the use of creative learning media and adaptive evaluation strategies to increase the effectiveness of integrated thematic learning at the elementary school level, especially in science learning content.